The Stability of Supply and Rice Price in Sukoharjo Regency - Ekowati, Titik; Prasetyo, Edy; Mukson, Mukson (AGRARIS: Journal of Agribusiness and Rural Development Research, 2020)
The economic conditions of rice, whether aspect of supply, demand, or rice price is continue to fluctuate due to changes of the phenomena. Therefore, this commodity needs to be examined in regarding its supply, demand and price aspects. This study aims to analyze the supply and price stability of rice. The study used a secondary data method. The study was conducted in Tawangsari and Mojolaban Districts of Sukoharjo Regency. Data were analyzed by Co variance analysis. The study results showed that supply and rice consumption were surplus and stable. The stability of prices and supply for paddy and rice is occurred in Tawangsari and Mojolaban Districts and Sukoharjo regency as well.